Analysis of PV Cell-based DG involving Improved Power Quality Converter for voltage control (International Journal of Engineering and Computer Science, 2017)
The research investigated the impact on the power system with an extensive penetration of photovoltaic (PV) generation. A model of PV generation suitable for studying its interactions with the power system was developed. The dynamic response of a PV generation system to rapid changes in irradiance was investigated. An aggregated model of grid-connected PV generation was built, and it was used for simulating the integration of PV generation on a large-scale. Voltage control technique was investigated by simulation. Distributed Generation (DG) units are connected to the grid increasing nowadays for several reasons. Most DG units are relatively small and connected to the distribution network. A large part of the DG units connected to the grid via power electronic converters. The main task of the converters is to convert the power that is available from the prime source to the correct voltage and frequency of the grid. The general objective of this paper is to investigate how the power electronic converters can support the grid and solve power quality problems. An IEEE-5 bus system considered for this work to validate the power electronic converter using MATLAB/ Simulink.